2018
DOI: 10.1049/mnl.2017.0502
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stamp design on residual layer thickness and contact pressure in UV nanoimprint lithography

Abstract: Pattern density is an important factor in UV nanoimprint stamp design. Various pattern densities may affect the thickness of the residual layer and its uniformity. This work investigated the effect of pattern density as well as other stamp parameters, including stamp material, stamp thickness and cavity height, on residual layer thickness (RLT), contact pressure, and imprint quality. Two kinds of stamps were designed for simulation, one with detached uniform lines and the other with adjacent non-uniform lines.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Defects in the conformal stamp-substrate contact due to edge imperfections and reduced contact pressure around the channel edges aggravate the effect. 37 Figure 2E is a transmission electron micrograph of a plasmatreated line on a silicon substrate. The change of the crosssectional profile during plasma sintering was minor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Defects in the conformal stamp-substrate contact due to edge imperfections and reduced contact pressure around the channel edges aggravate the effect. 37 Figure 2E is a transmission electron micrograph of a plasmatreated line on a silicon substrate. The change of the crosssectional profile during plasma sintering was minor.…”
Section: Resultsmentioning
confidence: 99%
“…Defects in the conformal stamp-substrate contact due to edge imperfections and reduced contact pressure around the channel edges aggravate the effect. 37 …”
Section: Resultsmentioning
confidence: 99%
“…Although we have demonstrated that a variable imprint depth provides an additional degree of freedom in creating plasmonic colouration, in many applications this can be undesirable. Several approaches have been proposed to reduce the global variation of imprint depth such as increasing the applied pressure, 42 increasing the imprinting time, 31,43 introducing additional microcavities or protrusions in proximity to the original design 33 and utilising a cavity-equalized mould. 36 To address this issue, we propose the addition of a novel mesh-like microcavity architecture to the multi-density mould to facilitate resist ow.…”
Section: Resultsmentioning
confidence: 99%
“…While pressure variations due to pattern density can be remedied by modeling the stamp design [38,39], another non-negligible effect came from the nanoimprinting tool. Any roughness present on the printer plates resulted in defects in the imprinted regions.…”
Section: Thermal Nilmentioning
confidence: 99%